Masalah Budaya Dan Lintas Budaya Yang Terlihat Dalam Perintisan Gereja - Megawati Manullang; Erickson Nanda Putra Halawa; Lela Siska Inriani Samosir; Titin Wulandari Malau (Jurnal Silih Asah, 2024)
Cultural issues cannot be separated from the church planting process. This research uses a literature detective method to analyze cultural and cross-cultural problems seen in church planting. The church, as a religious institution with a long history, continues to transform with changing times. Church planting, as the process of establishing a new community, is not only about physical construction, but also organizing a community of faith. In this process, culture has an important role, bringing challenges and opportunities that need to be understood scientifically. Culture plays a significant role in church planting. Cultural influences can pose challenges, such as differences in values, traditions, and social norms that can hinder acceptance of new religious messages. However, cross-culturalism in church planting also carries great potential to facilitate the spread of the gospel and win the hearts of local residents through an approach that understands local culture. With wise strategy and proper contextualization, the church can bridge the gospel and culture in its mission.